Unorthodox Kin : Portuguese Marranos and the Global Search for Belonging - Leite, Naomi, 1972- (Book collections on Project MUSE., 2017)
"Unorthodox Kin is a groundbreaking exploration of identity, relatedness, and belonging in the context of profound global interconnection. Naomi Leite tells the gripping story of Portugal's urban Marranos, who trace their ancestry to fifteenth-century Jews forced to convert to Catholicism, as they come to understand their place within the Jewish world. Focusing on the work of imagination and face-to-face encounters between urban Marranos and Jewish tourists and outreach workers, Leite deftly examines how perceptions of self, kinship, and belonging evolve across local and global social spaces. An ethnography of affinities, the book maps diverse contexts and criteria by which people come to identify with a particular social category, the forms of interaction that give rise to alienation or affiliation, and practices through which some are made strangers and others kin. Beautifully written and methodologically innovative, Unorthodox Kin is a model study for the anthropology of kinship, tourism, religion, and globalization."--Provided by publisher.